Answer:
18q^2 - 52q + 32
Step-by-step explanation:
We can use the Distributive Property to solve this.
(2q-4)(9q-8)
2q(9q) + 2q(-8) + -4(9q) + -4(-8)
18q^2 - 16q - 36q + 32
18q^2 - 52q + 32
18q^2 - 52q + 32
Find f(-2) f(x)=9x^2-5x+2
f(-2) means replace x in the equation with -2:
f(-2)=9(-2)^2-5(-2)+2
= 9(4) +10 + 2
= 36 +10 + 2
= 48
f(-2) = 48
(11 + 21) - ( 3 - 100 )
= 32 + 97
= 129
or (11+21)-(3+100)
= 32 - 103
= - 71
I have no idea about your topic but hope it's right! Good luck
Answer:
-13x^2 + 6x + 11
Step-by-step explanation:
Just subtract the numbers that are similar (i.e. -5x^2 - 8x^2)